(untitled) (Singaporean Journal of Business Economics and Management, 2017)
Small and Micro Enterprises (SMEs) play an important economic role in many countries. Despite this fact, SMEs faced many threats where the lack of credit is identified as one of the most serious constraints facing SMEs and hindering their development (Oketch, 2000; Tomecko & Dondo, 1992; Kiiru, 1991) among others. In this regard, the government of Ethiopia established several micro finance institutions (MFIs) including Amhara Credit and Saving Institution (ACSI) towards resolving the credit access problem of Small and Micro Enterprises (SMEs). In spite of rapid expansion of microfinance services by ACSI in the last one decade or so in the Amhara region of Northern Ethiopia, currently reaching more than 550,000 credit clients, there has been little attempt to measure the service quality it renders to its clients. The objective of the study was to see whether the institutional vision of ’bringing quality service’ is attained or not taking small and micro business enterprise owners, one segment of ACSI credit clients and also to identify the failure if any with regarding the quality parameters. The SERVQUAL model (developed by Parasuraman et al., 1991) is used for the study. The model begins with the assumption that individuals are able to articulate both their expectations of the general characteristics and determinants of quality service and also their perceptions of actual and current service quality for a specific service provider. Both ’quantitative’ and ’qualitative’ methods were used to collect data from over 85 small and micro business enterprise owners selected using purposive sampling technique to incorporate at least the major business engagement areas in the city. As a brief summary of the study, Amhara Credit and Saving Institution failed to meet the service expectation of small and micro business owners for all dimensions. Among the dimensions of service quality highest negative gap belongs to empathy. Furthermore, relative importance (weight) of quality dimensions stated by SMEs is highest for reliability.